1999
DOI: 10.1090/s0025-5718-99-01145-x
|View full text |Cite
|
Sign up to set email alerts
|

Random Fibonacci sequences and the number $1.13198824\dots$

Abstract: For the familiar Fibonacci sequence (defined by f 1 = f 2 = 1, and fn = f n−1 + f n−2 for n > 2), fn increases exponentially with n at a rate given by the golden ratio (1 + √ 5)/2 = 1.61803398. .. . But for a simple modification with both additions and subtractions-the random Fibonacci sequences defined by t 1 = t 2 = 1, and for n > 2, tn = ±t n−1 ± t n−2 , where each ± sign is independent and either + or − with probability 1/2-it is not even obvious if |tn| should increase with n. Our main result is that n |t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 37 publications
1
70
0
2
Order By: Relevance
“…This definition is equivalent to ours only in the case p = 1/2, which explains why the graph of the Lyapunov exponent drawn on Fig. 5 in [11] is different from our Fig. 2.…”
Section: Extension To Viswanath's Settingmentioning
confidence: 54%
See 1 more Smart Citation
“…This definition is equivalent to ours only in the case p = 1/2, which explains why the graph of the Lyapunov exponent drawn on Fig. 5 in [11] is different from our Fig. 2.…”
Section: Extension To Viswanath's Settingmentioning
confidence: 54%
“…In the case p = 1/2, (|F n |) and ( F n ) have the same distribution law as the sequence (|t n |) studied by Viswanath [11]. In his paper, using Furstenberg's formula [4] (see also [1,Chap.…”
Section: Introductionmentioning
confidence: 96%
“…While traditional integer sequences are deterministic, there is a growing interest in stochastic counterparts of fundamental sequences and their relevance to disordered or random systems. For example, the random Fibonacci sequence x n = x n−1 ± x n−2 [2,3,4] has links with various topics in condensed matter physics, dynamical systems, products of random matrices, etc. (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of cell division for bacteria is a random process; there will be a certain percentage of cells that are dividing in any time, which is different from the Fibonacci sequence [25]. Recently, the research of Viswanath et al indicated that RC for a random system will be approximately 1.133 [26,27]. It follows the patterns of random cell division, which has been confirmed by a mathematical modeling approach [20].…”
Section: Employing Rc Changes For Growth Sequence Turbidity To Characmentioning
confidence: 93%
“…According to Fibonacci sequence analysis [25][26][27], we propose a method for AST that used the RC (recurrent coefficient for a growing sequence) of bacterial turbidity as the objective function, and therefore, the impact of composition heterogeneity of bacteria on AST will be well characterized. This method is expected to be developed into one commonly used method for pharmacodynamics in AST [28].…”
mentioning
confidence: 99%